2021
DOI: 10.1172/jci.insight.144561
|View full text |Cite
|
Sign up to set email alerts
|

Circulating nuclear DNA structural features, origins, and complete size profile revealed by fragmentomics

Abstract: To unequivocally address their unresolved intimate structures in blood, we scrutinized the size distribution of circulating cell-free DNA (cfDNA) using whole-genome sequencing (WGS) from both double- and single-strand DNA library preparations (DSP and SSP, n = 7) and using quantitative PCR (Q-PCR, n = 116). The size profile in healthy individuals was remarkably homogenous when using DSP sequencing or SSP sequencing. CfDNA size profile had a characteristic nucleosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
88
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 59 publications
6
88
0
Order By: Relevance
“…This process has also provided the following observations: (i), jagged dsDNA appeared by far the most present cirDNA structural forms; (ii), the lowest cirDNA fragment size is about 70 bp; and (iii), this might be due to the low hybridization forces of the lower-sized jagged fragments leading to their peeling off from histone/nucleosome particles (29). Altogether, our data suggest that the proportion of cir-nDNA inserted in mono-nucleosomes, di-nucleosomes, and chromatin of higher molecular size (<1000 bp) in healthy individuals ranges from 67 to 80%, from 9 to 12%, and from 8 to 21%, respectively (29).…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…This process has also provided the following observations: (i), jagged dsDNA appeared by far the most present cirDNA structural forms; (ii), the lowest cirDNA fragment size is about 70 bp; and (iii), this might be due to the low hybridization forces of the lower-sized jagged fragments leading to their peeling off from histone/nucleosome particles (29). Altogether, our data suggest that the proportion of cir-nDNA inserted in mono-nucleosomes, di-nucleosomes, and chromatin of higher molecular size (<1000 bp) in healthy individuals ranges from 67 to 80%, from 9 to 12%, and from 8 to 21%, respectively (29).…”
Section: Discussionmentioning
confidence: 96%
“…Subsequent works using WGS analysis confirmed this in greater detail (2527,50,51). In addition, WGS-assisted fragmentomics revealed nucleosome footprints, which indicated that detected short fragments (30 to 400 bp) derive from the nucleosome around which cirDNA is packed and relatively stabilized in the blood compartment (25,27,29). Furthermore, Shendure’s team (25) inferred tissue of origins from nucleosome occupancy as determined by WGS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations